Lithium secondary battery

JP7645292B2Active Publication Date: 2025-03-13LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022580498
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-26
Filing Date
2022-02-23
Publication Date
2025-03-13
Estimated Expiration
2042-02-23

AI Technical Summary

Benefits of technology

【0012】 本発明によるリチウム二次電池は、負極に含まれたLi‐Mg合金と電解質に含まれたフラン系溶媒によってリチウム樹状の成長を抑制し、リチウムと電解質の副反応を抑制し、電池の寿命特性を改善することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645292000003
    Figure 0007645292000003
  • Figure 0007645292000004
    Figure 0007645292000004
  • Figure 0007645292000005
    Figure 0007645292000005
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery, and more particularly, the lithium secondary battery can improve battery life characteristics by suppressing lithium dendritic growth and side reactions between polysulfides generated from the positive electrode and the lithium negative electrode due to the interaction between a Li-Mg alloy contained in the negative electrode and a furan-based solvent contained in the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 2021-0026115 filed on February 26, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated as part of this specification.

[0002] The present invention relates to a lithium secondary battery. [Background technology]

[0003] Lithium-sulfur secondary batteries are secondary batteries that contain lithium metal, which has a large theoretical capacity, as an anode active material and sulfur as a cathode active material, and have the advantage of being able to realize a higher energy density than existing lithium secondary batteries.

[0004] However, there are several issues that must be resolved before lithium-sulfur secondary batteries can be commercialized. First, dendrites can form as lithium is deposited on the negative electrode during charging, which can cause a short circuit between the negative and positive electrodes. Second, the positive electrode active material dissolves in the electrolyte in the form of lithium sulfide (LiPS) and shuttles to the negative electrode, forming a lithium-sulfur compound, which can cause loss of the positive electrode active material and immobilization of the negative electrode.

[0005] To solve these problems, it is necessary to develop a new lithium composite material that can control the lithium dendrite while introducing an anode protective layer that can prevent side reactions between lithium and sulfur, or that can improve the diffusion on the lithium surface to enable uniform lithium deposition.

[0006] Korean Patent Publication No. 10-2020-0007081 discloses a new lithium composite material applied to the anode (negative electrode) of an electrochemical cell, which is a solid solution of lithium and one or more non-lithium metals. The non-lithium metal forms a solid solution with lithium to perform the function of a current collector, but it still shows limitations in suppressing the formation of lithium dendrites and the emergence of polysulfides, which are problems in lithium-sulfur secondary batteries.

[0007] Therefore, there remains a need to develop new lithium composite materials that can suppress the formation of lithium dendrites and the side reactions between lithium and sulfur in lithium secondary batteries. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 10-2020-0007081 Summary of the Invention [Problem to be solved by the invention]

[0009] Here, in order to solve the problems of the conventional technology, the present inventors have confirmed that when a lithium alloy is used as a lithium negative electrode active material and a furan-based solvent is used as an electrolyte solvent, the growth of lithium dendrites in the lithium negative electrode can be suppressed, and even if sulfur is contained in the positive electrode active material, a side reaction between lithium and sulfur can be suppressed, thereby improving the life characteristics of the battery.

[0010] SUMMARY OF THE PRESENTLY PREFERRED EMBODIMENTS An object of the present invention is to provide a lithium secondary battery capable of improving the life characteristics of the battery by suppressing the formation of lithium dendrites at the negative electrode and suppressing the side reaction between lithium and sulfur at the positive electrode. [Means for solving the problem]

[0011] To achieve the above object, the present invention provides a lithium secondary battery including a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode includes LiMg, and the electrolyte includes a furan-based solvent, a lithium salt, and an additive. Effect of the Invention

[0012] The lithium secondary battery according to the present invention can improve the life characteristics of the battery by suppressing the growth of lithium dendrites and side reactions between lithium and the electrolyte due to the Li-Mg alloy contained in the negative electrode and the furan-based solvent contained in the electrolyte. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic diagram showing the crystal structures of a Li-Mg alloy and a Li-Al alloy (or a Li-Zn alloy). [Figure 2a] 2a and 2b are graphs showing the life characteristics of Example 1 and Comparative Examples 1 to 5. [Figure 2b] 2a and 2b are graphs showing the life characteristics of Example 1 and Comparative Examples 1 to 5. [Diagram 3] 1 shows optical photographs and 3D stereoscopic photographs of the negative electrode surfaces of Example 1 and Comparative Example 4. [Figure 4a] 4a and 4b show cross-sectional SEM (scanning electron microscope) photographs and EDS (Energy Dispersive X-ray Spectroscopy) analysis results for the negative electrodes of Example 1 and Comparative Example 4, respectively. [Figure 4b] 4a and 4b show cross-sectional SEM (scanning electron microscope) photographs and EDS (Energy Dispersive X-ray Spectroscopy) analysis results for the negative electrodes of Example 1 and Comparative Example 4, respectively. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will now be described in more detail to aid in understanding the invention.

[0015] The terms and words used in this specification and claims should not be construed in a limited manner based on their ordinary or dictionary meaning, but should be interpreted in a meaning and concept that corresponds to the technical idea of ​​the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.

[0016] Lithium secondary battery The present invention relates to a lithium secondary battery including a positive electrode, a negative electrode, a separator, and an electrolyte, the negative electrode including a Li-Mg alloy, and the electrolyte including a furan-based solvent, a lithium salt, and an additive.

[0017] The Li-Mg alloy can increase the diffusion of lithium ions on the surface of the negative electrode to suppress the growth of lithium dendrites, and can adsorb polysulfides generated at the positive electrode to control side reactions between lithium and electrolytes.

[0018] The furan-based solvent forms a protective layer on the surface of the negative electrode containing the Li-Mg alloy as the rings of the furan component are decomposed, thereby reducing side reactions and improving the life of the lithium secondary battery.

[0019] In the present invention, the Li-Mg alloy is a solid solution of lithium and magnesium, and a solid solution means a solid mixture having a completely uniform phase.

[0020] Mg is an alloying element that can form a solid solution with Li. Li-Mg alloys are particularly used as negative electrode active materials in lithium secondary batteries to suppress the growth of lithium dendrites and adsorb polysulfides to suppress side reactions between lithium and electrolytes.

[0021] FIG. 1 is a schematic diagram showing the crystal structures of a Li-Mg alloy and a Li-Al alloy (or a Li-Zn alloy).

[0022] As shown in Figure 1, Li-Mg alloy has Mg atoms uniformly distributed among Li atoms in the crystal structure. Mg shows high solid solubility in Li. Therefore, Mg does not form a new phase such as an intermetallic compound in the Li crystal structure, but can substitute for existing Li sites to form a solid solution.

[0023] Meanwhile, in the case of alloys, Li-Al alloys or Li-Zn alloys, Al atoms or Zn atoms form new heterometallic compounds within Li atoms in the crystal structure. The heterometallic compounds exist in a form of segregation at localized specific positions such as grain boundaries of particulate Li, and form new phases without mixing with lithium, so that the effect of the alloy may be ineffective. At this time, new heterometallic compounds may be formed in various forms depending on the ratio between elements. For example, the Li-Al alloy may be Li9Al4, Li3Al2, etc., and the Li-Zn alloy may be LiZn, Li2Zn3, etc.

[0024] Also, the solid solubility of Mg in the Li-Mg alloy may be more than 0 wt% and less than 90 wt% (more than 0 at% and less than 70 at%). Here, the solid solubility means the weight of Mg contained in the Li-Mg alloy in the form of a solid solution. If the solid solubility of Mg is 0 wt%, the effect of suppressing lithium dendritic growth and the effect of suppressing the side reaction between lithium and sulfur are negligible, and if it exceeds 90 wt%, the crystal structure of lithium cannot be maintained, and the negative electrode active material becomes Mg metal with a different crystal structure other than lithium, and the capacity of the battery may be reduced due to the reduction in the capacity of the lithium active material. The Mg metal with a different crystal structure may be, for example, α-Mg.

[0025] In the lithium secondary battery according to the present invention, the negative electrode may include a Li-Mg alloy as a negative electrode active material. The Li-Mg alloy not only functions as a basic negative electrode active material as described above, but also inhibits the growth of lithium dendrites and prevents a side reaction between lithium and sulfur. The Li-Mg alloy may be in the form of a foil made of individual particles.

[0026] The negative electrode active material layer itself can act as a negative electrode current collector, but it can also be formed on a negative electrode current collector separately to reduce the resistance of the battery. The negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. The negative electrode current collector can have a thickness of typically 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector can be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0027] The thickness of the negative electrode may be more than 0 μm and less than 200 μm, specifically, more than 0 μm, 50 μm or more, or 80 μm or more, or 120 μm or less, 150 μm or less, or 200 μm or less. In this case, the thickness of the negative electrode may be the thickness of a Li-Mg alloy, and when the thickness falls within the above-specified thickness range, it is preferable because it can suppress the growth of lithium dendrites and prevent the eruption of polysulfides from the positive electrode.

[0028] In the lithium secondary battery according to the present invention, the positive electrode may include a positive electrode active material layer, and the positive electrode active material layer may include a positive electrode active material, a binder, and a conductive material.

[0029] The positive electrode active material may contain one or more selected from the group consisting of inorganic sulfur, Li2Sn (n ≧ 1), disulfide compounds, organic sulfur compounds, and carbon-sulfur polymers. The positive electrode active material can be contained in an amount of 70 to 95% by weight based on the total weight of the positive electrode active material layer. Further, in addition to the positive electrode active material, an additional positive electrode active material can also be included. The additional positive electrode active material is not particularly limited as long as it is a commonly used positive electrode active material for lithium secondary batteries. For example, as the additional positive electrode active material, for example, LiCoO2, LiNiO2, LiMnO2, LiMn2O2, Li(Ni a Co b Mn c )O2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), LiNi 1‐d Co d O2, LiCo 1‐d Mn d O2, LiNi 1‐d Mn d O2 (0 ≦ d < 1), Li(Ni a Co b Mn c )O4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2‐e Ni e O4, LiMn 2‐e Co e O4 (0 < e < 2), LiCoPO4, or LiFePO4, etc. can be mentioned, and any one or a mixture of two or more of these can be used.

[0030] The conductive material is used to give conductivity to the positive electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing a chemical change in the battery. Specific examples include carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; graphite such as natural graphite and artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and among these, one type alone or a mixture of two or more types can be used. The conductive material can be included in an amount of 1 wt % to 20 wt % based on the total weight of the positive electrode active material layer.

[0031] The binder also serves to improve adhesion between the positive electrode active material particles and between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 wt% to 20 wt% based on the total weight of the positive electrode active material layer.

[0032] In the lithium secondary battery according to the present invention, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, a separator having low resistance to ion movement of the electrolyte and excellent moisture absorption ability of the electrolyte is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, etc. may be used. In addition, a separator coated with a ceramic component or a polymer material to ensure heat resistance or mechanical strength may be used, and may be selectively used in a single layer or multilayer structure.

[0033] In the lithium secondary battery according to the present invention, the electrolyte may include a furan-based solvent, a lithium salt, and an additive.

[0034] The furan-based solvent is a heterocyclic compound containing one or more double bonds, and specifically includes, for example, furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzofuran, 2-( It may contain one or more selected from the group consisting of 2-(2-nitrovinyl)furan (thiophene), thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene, and 2,5-dimethylthiophene, and preferably may contain one or more selected from the group consisting of 2-methylfuran and 2-methylthiophene.

[0035] The furan-based solvent may further include an additional organic solvent, and the additional organic solvent may include dimethoxyethane (DME); ester-based solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether-based solvents such as dibutyl ether and tetrahydrofuran; ketone-based solvents such as cyclohexanone; aromatic hydrocarbon-based solvents such as benzene and fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), and propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as ethylene carbonate (PC); alcohol-based solvents such as ethanol and isopropyl alcohol; nitriles such as R-CN (R is a C2 to C20 straight-chain, branched or cyclic hydrocarbon group that can include a double bond oriented ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane (DOL); or sulfolanes. Preferably, the furan-based solvent may include a mixed solvent of 2-methylfuran (2ME-F) and dimethoxyethane (DME).

[0036] In addition, the lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyyl)imide), LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, LiC(CF3SO2)3, (CF3SO2)2NLi, (FSO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium 4-phenylborate, and lithium imide. The lithium salt is preferably used at a concentration in the range of 0.1M to 2.0M. If the lithium salt concentration is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0037] Also, the additive may include a nitrate-based compound, which may be selected from lithium nitrate (Li(NO3), lithium nitrate), potassium nitrate (KNO3), cesium nitrate (CsNO3), magnesium nitrate (Mg(NO3)2), barium nitrate (Ba(NO3)2), potassium nitrite (KNO2), and cesium nitrite (CsNO2). At this time, the additive may be included in an amount of 0.1 wt % to 10 wt % based on the total weight of the electrolyte.

[0038] In addition to the nitric acid-based compound, the additive may further include one or more additives such as haloalkylene carbonate-based compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0039] As described above, the lithium secondary battery according to the present invention stably exhibits excellent discharge capacity, output characteristics and capacity maintenance rate, and therefore can be used as a device power source in portable devices such as mobile phones, notebook computers, and digital cameras, and in electric vehicles such as hybrid electric vehicles (HEVs).

[0040] Lithium-sulfur secondary battery The present invention also relates to a lithium-sulfur secondary battery.

[0041] The positive electrode of the lithium-sulfur secondary battery includes a sulfur-containing material, the negative electrode includes a Li-Mg alloy, the electrolyte solvent includes 2-methylfuran (2ME-F), and the lithium salt includes LiFSI. Specifically, the solvent is a mixture of 2-methylfuran (2ME-F) and dimethoxyethane (DME).

[0042] The negative electrode Li-Mg alloy and the electrolyte 2-methylfuran (2ME-F) can effectively inhibit the growth of lithium dendrites and inhibit the side reaction between lithium and sulfur, thereby improving the life characteristics of the battery.

[0043] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be obvious to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical idea of ​​the present invention. It is natural that such changes and modifications fall within the scope of the accompanying claims.

[0044] Example 1 1-1. Negative electrode manufacturing A 100μm thick Li-Mg alloy was prepared as the negative electrode. The Li-Mg alloy was alloyed with 1wt% Mg. It was heated and melt mixed with a lithium ingot so that the Mg content was about 1wt%, then cooled to room temperature and rolled with a roll press to produce a 100μm thick Li-Mg alloy foil, which was then used as the negative electrode. No separate current collector was used.

[0045] 1-2. Cathode manufacturing A sulfur-carbon composite was prepared by mixing sulfur and CNTs (carbon nanotubes) in a weight ratio of 75:25. After mixing the sulfur and CNTs, the mixture was heated and the sulfur was supported on the carbon composite by melt diffusion.

[0046] The positive electrode active material, conductive material, and binder, respectively, were mixed in a weight ratio of 87.5:5:7.5 in distilled water solvent to prepare a positive electrode slurry. The positive electrode slurry was applied to one side of an Al foil current collector, dried at 80°C, and rolled using a roll press to prepare a positive electrode. The loading of the positive electrode was 3 mg / cm. 2 It was made to be like this.

[0047] 1-3. Electrolyte production The electrolyte was prepared by adding 0.75M LiFSI (a lithium salt) and 35 wt% LiNO (an additive) to a mixed solvent (2ME-F:DME=1:4 (v / v)) made by mixing 2-methylfuran (2ME-F) and dimethoxyethane (DME) in a volume ratio of 1:4.

[0048] 1-4. Lithium-sulfur secondary battery manufacturing A porous polyethylene separator was inserted between the positive and negative electrodes, and stacked to assemble a pouch cell. An electrolyte was then injected and sealed to prepare a pouch cell type lithium-sulfur secondary battery.

[0049] Comparative Example 1 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 1, except that bare Li and DOL / DME (5:5 (v / v)) were used as the negative electrode and electrolyte solvent instead of Li-Mg alloy and 2ME-F / DME (2:8 (v / v)) (DOL: 1,3-Dioxolane).

[0050] Comparative Example 2 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 1, except that DOL / DME (5:5 (v / v)) was used as the negative electrode and electrolyte solvent instead of 2Me-F / DME (2:8 (v / v)) (DOL: 1,3-Dioxolane).

[0051] Comparative Example 3 A lithium-sulfur secondary battery was fabricated in the same manner as in Example 1, except that Li was used as the negative electrode instead of the Li-Mg alloy.

[0052] Comparative Example 4 A lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that a Li-Al alloy (Al 1 wt %) was used as the negative electrode instead of the Li-Mg alloy.

[0053] Comparative Example 5 A lithium-sulfur secondary battery was manufactured in the same manner as in Example 1, except that a Li-Zn alloy (Zn 5 wt %) was used as the negative electrode instead of the Li-Mg alloy.

[0054] Experimental Example 1 The pouch cell-type lithium-sulfur secondary batteries prepared in Example 1 and Comparative Examples 1 to 5 were operated at 25° C. with a 0.2 C charge / 0.3 C discharge cycle in CC (constant current) mode, and then the physical properties including the discharge capacity were measured. The results are shown in Table 1 and FIGS. 2a and 2b.

[0055] [Table 1]

[0056] As shown in Table 1, FIGS. 2a and 2b, the life characteristics of Example 1 were significantly superior to those of Comparative Examples 1 to 5.

[0057] Comparative Examples 3, 4, and 5 contained the same 2Me-F / DME solvent as the electrolyte solvent in Example 1, but contained bare Li, Li-Al alloy, and Li-Zn alloy as the negative electrode, respectively, and the life characteristics were inferior to those of Example 1.

[0058] This result is because in Example 1, Li and Mg form a solid solution, so that Mg does not form a separate heterometallic compound in the lithium anode and is uniformly distributed at the atomic level, and this uniform distribution of Mg more effectively suppresses the formation of lithium dendrites and uniformly performs lithium growth and stripping. On the other hand, the Li-Al alloy and Li-Zn alloy of Comparative Example 4 and Comparative Example 5 form heterometallic compounds such as Li9Al4 and LiZn, and the alloy elements are segregated in local regions such as lithium grain boundaries in the form of non-uniform particles, which is not effective in suppressing lithium dendrites and uniform growth and stripping of lithium.

[0059] This confirmed that lithium-sulfur secondary batteries containing LiMg in the negative electrode and a mixed solvent containing the furan-based solvent 2-methylfuran (2ME-F) as the electrolyte solvent have good life characteristics.

[0060] The pouch cell type lithium-sulfur secondary batteries prepared in Example 1 and Comparative Example 4 were operated in CC mode at 25° C. with a 0.2 C charge / 0.3 C discharge cycle. After 120 cycles, physical properties such as SOC (State of charge) 100 and discharge capacity retention rate were measured by the following methods, and the results are shown in Table 2 below.

[0061] (1) Discharge capacity maintenance rate After 120 cycles, the capacity was calculated as a percentage of the initial capacity.

[0062] (2) Thickness of the negative electrode The thickness of the negative electrode was measured using a thickness measuring device (TESA, μ-hite).

[0063] (3)Negative electrode porosity rate The negative electrode porosity was calculated based on the following formula 1.

[0064] <Formula 1> Negative electrode porosity (%) = 100 × [1 - (negative electrode density after operation) / negative electrode density before operation)]

[0065] In Equation 1, the negative electrode density was calculated by dividing the weight per unit area of ​​the negative electrode by its thickness.

[0066] (4) Average roughness and maximum step The average roughness and maximum step height were measured using a laser microscope (KEYENCE VK-X100 Series).

[0067] [Table 2]

[0068] As shown in Table 2, Example 1, in which the negative electrode of the lithium-sulfur secondary battery contains LiMg, shows a high discharge capacity retention rate even after 120 cycles of operation, and shows a low thickness increase rate, a low negative electrode porosity rate, and a low average roughness. It can be seen that the low negative electrode porosity rate and uniform surface maintenance are the reasons for the improved battery life.

[0069] 3 shows optical photographs and 3D stereoscopic photographs of the surfaces of the negative electrodes of Example 1 and Comparative Example 4. The negative electrodes of Example 1 and Comparative Example 4 were in a state of SOC 100 after the 120 cycles. The optical photographs and 3D stereoscopic photographs were taken using a laser microscope (KEYENCE VK-X100 Series).

[0070] 3, most of the area of ​​the anode containing the Li-Al alloy of Comparative Example 4 was degenerated, and the difference in level was very large. On the other hand, the anode containing the Li-Mg alloy of Example 1 maintained lithium metal over 80% of the total area, and the difference in level was low, confirming that the physical structure of the anode was maintained in a stable state.

[0071] 4a and 4b show cross-sectional SEM (scanning electron microscope) photographs and EDS (Energy Dispersive X-ray Spectroscopy) analysis results for the negative electrodes of Example 1 and Comparative Example 1, respectively. The negative electrodes of Example 1 and Comparative Example 1 are in a state of SOC 100 after 120 cycles. SEM photographic measurements and EDS analysis were performed using a SEM-EDS (JEOL FESEM, JSM-7610F). No sulfur was detected in either Example 1 or Comparative Example 4 before operation.

[0072] As shown in FIG. 4a and FIG. 4b, in the negative electrode of the Li-Mg alloy of Example 1, Mg was still uniformly distributed in the lithium metal negative electrode even after 120 cycles of operation, whereas in the negative electrode of the Li-Al alloy of Comparative Example 4, a by-product containing a large amount of sulfur was formed due to a side reaction between lithium and sulfur, which is a positive electrode active material.

[0073] From this, it was confirmed that in the negative electrode of the Li-Mg alloy of Example 1, Mg forms a solid solution together with Li and is uniformly distributed, thereby suppressing the side reaction between lithium and sulfur.

[0074] Although the present invention has been described above with reference to limited embodiments and drawings, the present invention is not limited thereto, and it is of course possible for a person having ordinary skill in the art to which the present invention pertains to make various modifications and variations within the technical spirit of the present invention and the equivalent scope of the following claims.

Claims

1. A lithium secondary battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, the positive electrode includes a positive electrode active material, the positive electrode active material being a sulfur-carbon composite including sulfur and CNTs; the negative electrode comprises a Li-Mg alloy; The electrolyte comprises a heterocyclic compound containing one or more double bonds, a lithium salt, and an additive, The thickness of the Li-Mg alloy is 80 μm or more and 120 μm or less, The heterocyclic compound containing one or more double bonds includes at least one selected from the group consisting of furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, and 2,5-dimethylfuran; The additive is lithium nitrate (Li(NO 3 ), lithium nitrate), potassium nitrate (KNO 3 ), Cesium nitrate (CsNO 3 ), magnesium nitrate (Mg(NO 3 ) 2 ), barium nitrate (Ba(NO 3 ) 2 ), potassium nitrite (KNO 2 ) and cesium nitrite (CsNO 2 ) one or more types selected from the group consisting of lithium secondary batteries.

2. 2. The lithium secondary battery according to claim 1, wherein the Li-Mg alloy is a solid solution containing more than 0 wt % and less than or equal to 90 wt % Mg.

3. 3. The lithium secondary battery according to claim 1, wherein the Li-Mg alloy is in the form of a foil.

4. The lithium secondary battery according to any one of claims 1 to 3, wherein the heterocyclic compound containing one or more double bonds includes 2-methylfuran.

5. The lithium salts include LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiCl, LiBr, LiI, and LiClO. 4 , LiBF 4 , LiB 10 C 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN, LiC(CF 3 SO 2 ) 3 5. The lithium secondary battery according to claim 1, which contains at least one selected from the group consisting of lithium chloroborane, lithium lower aliphatic carboxylate, lithium 4-phenylborate, and lithium imide.

6. The additive is lithium nitrate (Li(NO 3 6. The lithium secondary battery according to claim 1, comprising:

Citation Information

Patent Citations

  • Electrolyte for lithium secondary battery and lithium secondary battery containing the same

    JP2018519620A

  • KR10‐2020‐0007081

  • Electrolyte for lithium-sulfur battery and lithium-sulfur battery comprising same

    WO2020105981A1

  • System for an ionic liquid-based electrolyte for high energy battery

    WO2020124086A1